2016
DOI: 10.1016/bs.pbr.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience of inhibition for addiction medicine

Abstract: A core deficit in drug addiction is the inability to inhibit maladaptive drug-seeking behavior. Consistent with this deficit, drug-addicted individuals show reliable cross-sectional differences from healthy non-addicted controls during tasks of response inhibition accompanied by brain activation abnormalities as revealed by functional neuroimaging. However, it is less clear whether inhibition-related deficits predate the transition to problematic use, and, in turn, whether these deficits predict the transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…Namely, pre-morbid functional abnormalities may confer vulnerability to SUDs and drugs may have acute and prolonged effects on brain function, and some drug-induced abnormalities may persist through prolonged abstinence. Therefore, abstinence may not return individuals to pre-substance-use-disorder baselines, and pre-morbid baselines may be suboptimal treatment targets as they may not represent ‘normalizations’ of functional activity relative to healthy non-drug-users with low SUD-vulnerability (see (Moeller, Bederson, Alia-Klein, & Goldstein, 2016) for review of changes with substance-use onset and predictors of treatment outcome). These complexities underline the limits of using healthy case-comparisons to derive treatment targets and reinforce the importance of testing treatment-related change within substance abusers and relating these changes to treatment mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, pre-morbid functional abnormalities may confer vulnerability to SUDs and drugs may have acute and prolonged effects on brain function, and some drug-induced abnormalities may persist through prolonged abstinence. Therefore, abstinence may not return individuals to pre-substance-use-disorder baselines, and pre-morbid baselines may be suboptimal treatment targets as they may not represent ‘normalizations’ of functional activity relative to healthy non-drug-users with low SUD-vulnerability (see (Moeller, Bederson, Alia-Klein, & Goldstein, 2016) for review of changes with substance-use onset and predictors of treatment outcome). These complexities underline the limits of using healthy case-comparisons to derive treatment targets and reinforce the importance of testing treatment-related change within substance abusers and relating these changes to treatment mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acute aerobic exercise (cycling) decreased drug-craving in women and men undergoing residential treatment for methamphetamine use disorder (19), and chronic aerobic exercise (8-week treadmill interval training) decreased measures of depression in men and women undergoing residential treatment for an illicit substance use disorder (i.e., heroin, amphetamine, cannabis; 18). Recent studies have also shown that aerobic exercise during abstinence can offset deficits in inhibitory control (1920) that have been linked to relapse (60). …”
Section: Overview Of Clinical Findingsmentioning
confidence: 99%
“…For example, sex differences have been observed in physiologic and neuroendocrine response to stress and drug cue (Back et al, 2005; Fox and Sinha, 2009) as well as in neural responses regulatory behaviors including inhibitory control, cognitive flexibility and self control (Moeller et al, 2016; Potenza et al, 2012). Notably, these are all measures that have been associated with high risk of relapse and treatment outcomes (Back et al, 2005; Daughters et al, 2009; Fox and Sinha, 2009; Moeller et al, 2016; Sinha et al, 2006; Van Dam et al, 2014). Furthermore, while executive functions such as response inhibition and self control are critical for successful clinical outcome and relapse prevention (Aharonovich et al, 2006; Aharonovich et al, 2003), these functions are known to be most compromised under stress and cue reactivity states.…”
Section: 0 Introductionmentioning
confidence: 99%